Biofuels and inclusive development: the Brazilian experience. Issue 2 (17th February 2017) - Flexor, Georges; Kato, Karina
ABSTRACT: This article addresses the question of whether the production and use of biofuels could be appropriate to support productive inclusion. After an overview of the main drivers of biofuels development in the last decade, the article analyses the Brazilian experience, the most ambitious programme to promote inclusive development through biofuel policy. It focuses on the institutional settings and its distributional effects, as well as the organisational dynamics in a semi-arid region, and concludes that even in a country like Brazil, with a long and successful tradition in biofuel policies, the productive inclusion of small-scale family farmers faces severe difficulties.